THE EFFECT OF ORGANIZATIONAL COMMITMENT AND WORK COMPETENCE ON EMPLOYEE PERFORMANCE OF PT TELKOM AKSES SURABAYA - Panjaitan, Dolfi Ishak; Sarmadi, Ahmad (EKOSSISTEM : Islamic Economics, Banking, Law, System, 2021)
This study aims to analyze the influence of Organizational Commitment and Work Competence on Employee Performance at PT Telkom Akses Surabaya. The telecommunications industry is highly dynamic, requiring employees who are not only competent but also have a high level of commitment. The research uses a quantitative approach with a survey method. The sample consisted of 68 employees selected purposively. Data were collected through questionnaires and analyzed using multiple linear regression with the help of SPSS 26. The results show that: (1) Organizational Commitment has a positive and significant effect on Employee Performance (β = 0.634; t = 7.159; Sig. 0.000); (2) Work Competence has a positive and significant effect on Employee Performance (β = 0.320; t = 3.713; Sig. 0.000); (3) Simultaneously, both variables have a significant effect on Employee Performance (F = 167.239; Sig. 0.000) with a contribution of 82.3% (R² = 0.823). These results prove that increasing commitment and competence together can improve employee performance. The company is recommended to develop programs to strengthen organizational commitment through employee engagement and to improve competence through continuous training to achieve optimal performance.